2011
DOI: 10.1007/s00134-011-2187-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sedation in intensive care unit: a randomized comparison between inhaled sevoflurane and intravenous propofol or midazolam

Abstract: Long-term inhaled sevoflurane sedation seems to be a safe and effective alternative to i.v. propofol or midazolam. It decreases wake-up and extubation times, and post extubation morphine consumption, and increases awakening quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
111
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 27 publications
(27 reference statements)
4
111
0
12
Order By: Relevance
“…5 These outcomes are attributable to the unique pharmacokinetic clearance of these agents (via pulmonary exhalation with minimal systemic accumulation) and bedside real-time end-tidal gas monitoring to aid dose titration. The role of volatile agents for ICU sedation requires further research, but this study confirmed that use of prolonged administration of these agents when using this active scavenging system can be done while maintaining workplace safety.…”
Section: To the Editormentioning
confidence: 99%
“…5 These outcomes are attributable to the unique pharmacokinetic clearance of these agents (via pulmonary exhalation with minimal systemic accumulation) and bedside real-time end-tidal gas monitoring to aid dose titration. The role of volatile agents for ICU sedation requires further research, but this study confirmed that use of prolonged administration of these agents when using this active scavenging system can be done while maintaining workplace safety.…”
Section: To the Editormentioning
confidence: 99%
“…Its applicability depends on the ICU staff and their background: Anesthetists handle volatile agents daily in the operating room (OR), are familiar with the concepts of end tidal concentration and minimum alveolar concentration, and are prepared in the unlikely event of a malignant hyperthermia reaction. The paper by Capdevila et al [18] in this issue of Intensive Care Medicine is welcome and shows the feasibility of sevoflurane anesthesia in uncomplicated ICU patients. The authors show that awakening and extubation times are much shorter with sevoflurane compared with those using midazolam or propofol.…”
mentioning
confidence: 96%
“…19 When compared with intravenous sedation, volatile sedation has been associated with shorter weaning times, 20 less ICU and hospital days, 21 and no difference in safety. 20,22,23 The anti-inflammatory properties of volatile anesthetics have been demonstrated in experimental (LPS-induced) lung injury. 12 However, little is known about the impact of sedatives on the course of ALI during mechanical BACKGROUND: Patients experiencing acute lung injury (ALI) often need mechanical ventilation for which sedation may be required.…”
mentioning
confidence: 99%